In vitro antifungal activity of Mimosa pudica rhizosphere bacteria against Fusarium spp. - Sriwulan, Sriwulan; Mustikaningrum, Dhina; Nurfitria, Nia (Universitas Muhammadiyah Surakarta, 2026)
This study aims to explore rhizosphere bacteria from Mimosa pudica L. as a source of antagonistic bacteria against Fusarium spp. Rhizosphere soil samples were collected, isolated, morphologically characterized, and tested for antifungal activity in vitro against Fusarium spp. The percentage of inhibition (PI) was calculated after 7 days. Six bacterial isolates were obtained and tentatively identified as Bacillus, Cellulomonas, Arthrobacter, and Micrococcus species. All isolates exhibited antagonistic activity against Fusarium spp., with inhibition percentages ranging from 61.99% to 81.83%. Isolate PM2 (tentatively identified as Cellulomonas) demonstrated the strongest inhibition at 81.83%, followed by isolate PM6 (tentatively identified as Micrococcus) at 79.25%. These results confirm the potential of Mimosa pudica L. as a source of biocontrol agents and warrant further investigation into their molecular identification, mechanisms of action, and in vivo efficacy.